KONSEP PERLINDUNGAN HAK KONSUMEN PADA PASAL 4 HURUF B UU NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DITINJAU DARI HUKUM ISLAM - Azizah, Ninik (Irtifaq, 2019)
This article intends to find out the concept of consumer protection inLaw No.8 of 1999 article 4 letter b concerning the right to choose goods and/orservices in accordance with the exchange rate, conditions, and guaranteespromised. Furthermore, the concept of consumer rights is reviewed through theperspective of Islamic law. According to the law, in consuming a product,consumers have the rights to make their choice. They may not get pressure fromoutsiders so that he is no longer free to buy or not to buy. If consumers are notcareful in choosing the desired product or service, then it will be the object ofbusiness activity that reap large profits and adverse sales methods, so thatconsumers become the object of exploitation by irresponsible business actors. Inaddition, consumers also need to get quality goods that are in accordance with theprices set and agreed upon. In market freedom, businesses can dictate the marketby increasing prices and consumers becoming victims of the lack of choice. Keywords: Consumer Rights, Consumer Protection, Islamic Law